Hubungan Antara Kemampuan Berpikir Kritis dengan Hasil Belajar melalui Model Inkuiri Terbimbing - Kusumasuti, Marianti Endrayana; Soerjanto, Soerjanto; Cholik, Mochamad (Jurnal Pendidikan Madrasah, 2024)
Critical thinking skills are essential skills in the learning process that can affect student learning outcomes. This study aims to analyze the relationship between critical thinking skills and student learning outcomes through the application of a guided inquiry learning model. The guided inquiry model was chosen because it encourages students to identify problems, formulate hypotheses, and find solutions independently with the guidance of teachers, thereby strengthening critical thinking skills. The results of the study showed that there was a significant positive correlation between students' critical thinking skills and their learning outcomes. Students who have good critical thinking skills show improved concept understanding, analytical skills, and higher learning outcomes compared to students who have low critical thinking skills. This study recommends the application of the guided inquiry model more widely to improve students' critical thinking skills and learning outcomes, especially in subjects that require problem-solving and in-depth analysis.